Effect of prenatal corticosteroids on the maturation of renal tubules in preterm infants - Jenny Ponce; Javier Cieza; Reyner Loza; Cristian León; Claudia Nuñez-Mochizaki (Brazilian Journal of Nephrology)
Abstract Introduction: The benefit of prenatal steroids in fetal lung maturation is well established, but their effect on the kidney has not been studied in detail in humans. Animal models have shown an increase in the expression of Na+/H+ exchangers, Na+-K+-ATPase pumps and aquaporin-1. This study aims to assess the effect of prenatal steroids on the maturation of renal tubules in preterms. Methods: 21 preterms born between 24 and 34 weeks were included. Participants were divided into two groups according to their exposure to prenatal steroids. The maturation of tubular function was evaluated through the change of the fractional excretion of Na+, K+ and beta 2-microglobulin, the transtubular gradient of K+, urine pH, and osmolality. Results: The mean age was 30.57 ± 1.8 weeks and the mean weight was 1415 ± 267.8 grams. Baseline differences were not observed, except for a significant difference in the change in urinary excretion of beta 2-microglobulin (Group 1: 1 980 ± 9 075 ng/mL and Group 2: –7 274 ± 10 006 ng/mL, p = 0.04). Conclusions: Prenatal steroids showed no statistically significant difference on renal tubule maturation in preterms.